Factores asociados a la deserción en la formación doctoral. El caso de la Universidad de los Andes, Colombia (2021)
This article shows dropouts factors in the doctoral students. The research is based on Universidad de los Andes case study, in Bogotá, Colombia. This is the first study in Colombia to analyze the dropout factors in an elite private university. Additionally, use a mixed methodology. On the one hand, with a quantitative analysis survival analysis with the Nelson - Aalen accumulated risk function and Hazard risk estimators. These analyzes were carried out with 719 records in the period 2010 - 2019. On the other hand, with a qualitative analysis of 15 interviews with active students and program directors, which were analyzed using coding. As results, it is shown that as the PhD program advances, the probability of dropping increases by up to 24%...